1991
DOI: 10.1063/1.461026
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton excitation, ionization, and dissociation decay dynamics of small clusters of niobium, tantalum, and tungsten: Time-resolved thermionic emission

Abstract: Articles you may be interested inCommunication: IR spectroscopy of neutral transition metal clusters through thermionic emission Selection of the substrate metal best for thermal positive ionization Rev. Sci. Instrum. 71, 856 (2000)Magic numbers in transition metal (Fe, Ti, Zr, Nb, and Ta) clusters observed by time-of-flight mass spectrometry J. Chem. Phys. 111, 235 (1999); 10.1063/1.479268 Thermionic electron emission of small tungsten cluster anions on the milliseconds time scaleThe ionization dynamics of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 66 publications
1
54
0
Order By: Relevance
“…Experimental measurements of electron autodetachment processes have been carried out for small organic molecules [11][12][13][14] and atomic clusters [15,16]. In these measurements, electron detachment occurred after vibrational heating via multiphoton infrared absorption.…”
Section: ϫmentioning
confidence: 99%
“…Experimental measurements of electron autodetachment processes have been carried out for small organic molecules [11][12][13][14] and atomic clusters [15,16]. In these measurements, electron detachment occurred after vibrational heating via multiphoton infrared absorption.…”
Section: ϫmentioning
confidence: 99%
“…6 For some of them, the lifetime can be hundreds of nsec, even tens of sec, and the most prominent example is C 60 . 14,15 There are also many reports for other molecules such as benzene, [16][17][18][19] benzene clusters, 20,21 benzene-noble gas dimers, 22 naphthalene, 23 azulene, 24 triethylamine, 25 ketene, 26 Nb, Ta, and W clusters, 27,28 C 70 , 14,29 fullerenes C n (nϽ96), 30 etc. There are many theoretical articles, too.…”
Section: Delayed Ionizationmentioning
confidence: 99%
“…31,32 If such an anion is formed under isolated conditions, the total internal energy of the system remains above the neutral ground state and the system may statistically detach the most weakly bound electron on a microsecond to millisecond timescale -known as thermionic emission. [33][34][35][36][37] Alternatively, some internally-hot anions may liberate excess internal energy through photoemission processes or by unimolecular dissociation to yield a stable anion.Using pump-probe femtosecond spectroscopy we have recently shown that a conjugated quinone, menadione, 26 can very efficiently produce ground electronic state anions following photoexcitation (or electron capture) with energies up to 3 eV above-threshold and probably higher. In menadione, the , is partly for experimental reasons and because the electron affinity is larger while maintaining a similar π-system.…”
mentioning
confidence: 99%
“…2, results from statistical electron emission from the ground electronic state of C 18 H 11 -. 26,[33][34][35][36][37] That is, excess internal energy statistically accumulates amongst certain modes leading to ejection of the most weakly bound electron. The properties, typical lifetimes (micro-to milliseconds), and mathematical description of thermionic emission have been well-reviewed in the aforementioned references.…”
mentioning
confidence: 99%